A Regulatory Risk-Based Approach to ATMP/CGT Development: Integrating Scientific Challenges With Current Regulatory Expectations - Salazar-Fontana, Laura I. (Frontiers in Medicine, 2022)
Cell & Gene Therapy Products (CGT), regulated as Advanced Therapy Medicinal Products (ATMP) in the European Union (EU), represent a novel and varied group of biotherapeutics developed to treat specific conditions for which there are limited effective treatments. The novelty and complexity of this product modality demands a regulatory risk-based approach to define a sound development plan, particularly, when most developers aim to target more than one market area simultaneously. This regulatory strategy should be built on solid scientific data that also addresses general regulatory recommendations to enable a benefit: risk analysis that is aligned with the particularities of each CGT product. This risk-based approach is especially helpful when no detailed product-specific regulatory guidelines are available. The goal of this article is to orient developers on how to build a combined EU/US regulatory strategy through the assessment of commonly understood quality (CMC), non-clinical, and clinical regulatory risks faced by ATMP/CGT.